Comorbidity assessment to determine prognosis in older adult patients with classical Hodgkin lymphoma. Issue 2 (3rd February 2020) - Galli, Eugenio; Cuccaro, Annarosa; Maiolo, Elena; Bellesi, Silvia; D'Alò, Francesco; Fusco, Domenico; Colloca, Giuseppe; De Stefano, Valerio; Hohaus, Stefan
Abstract: The clinical management of older adult patients with Hodgkin lymphoma (HL) remains a major challenge. The aim of this study was to evaluate the impact of comorbidity assessment according to a standardized approach, the Cumulative Illness Rating Scale (CIRS), on prognosis in patients with classical HL aged 60 years and older. We studied 76 consecutive older adult patients with HL (median age 69 y, range 60‐84) who had been treated in our institution between 1999 and 2018. Comorbidity was assessed at diagnosis according to CIRS. Anthracycline‐containing chemotherapy with curative intent was administered in 59 (78%) patients. We identified 41 (54%) patients with at least one severe comorbidity rated on CIRS grade ≥ 3. Patients with severe comorbidity were more likely to have advanced‐stage disease ( P = .003), to have an International Prognostic Score (IPS) > 3 ( P = .03), and to not receive anthracycline‐containing chemotherapy ( P = .008). The probability of overall survival (OS) at 3 years was 88% (95% CI, 71%‐95%) in patients without severe comorbidities, while it was only 46% (95% CI, 29%‐62%) in patients with a comorbidity CIRS grade ≥ 3 ( P = .0001). The impact of comorbidity on prognosis was also evident when restricting the analysis to patients treated with anthracycline‐containing therapy. The 3‐year OS was 93% (95% CI, 76%‐98%) ( P = .004) in patients without severe comorbidity and 72% (95% CI, 47%‐87%) in patients with severe comorbidity ( P = .004). In a multivariate analysis, presence of comorbidity, but not age, was a significant factor for OS. Therefore, we conclude that a significant proportion of older adult patients with HL has severe comorbidity on the CIRS scale, which impacts more importantly than age on prognosis.